(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: To describe the nephrotoxicity characteristics of patients using Colistin at Thong Nhat Hospital. Subjects and methods: Retrospective cohort study on 116 patients at Thong Nhat Hospital who were assigned to take colistin between June 1st, 2020 and December 31st, 2020. Results: Patients using colistin alone accounted for 30.17%. The majority of patients were treated with a combination of two antibiotics (colistin and another antibiotic). Nephrotoxicity accounted for 20.69% of the total studied patients. Median time to onset of nephrotoxicity in study patients was 8.5 days with interquartile range 5.5-15 days. The time range of onset of toxicity was mainly from 8 to 14 days, accounting for 45.83%. Distribution of patients with nephrotoxicity with the level of “Risk” accounted for the highest rate with 58.33%. There were 7 patients (29.17%) recovered during treatment, 2 patients (8.33%) had to undergo emergency dialysis. Conclusion: Nephrotoxicity accounted for 20.69%. The duration of onset of toxicity was mainly 8 to 14 days. Distribution of patients with nephrotoxicity with the level of “Risk” accounted for the highest rate with 58.33%.